Post-copulatory competition in a social monogamy system: Sperm morphology correlates with components of reproductive success - Carly E. Hawkins; Thomas P. Hahn; Jessica L. Malisch; Gail L. Patricelli (PLoS ONE, 2025)
Males in socially monogamous species can achieve reproductive success through multiple tactics– by defending paternity within the social nest and siring extra-pair offspring, or both. Previous studies have found that sperm morphology may differentially affect fertilization success in extra-pair compared to within-pair matings; therefore, we explored whether sperm morphological traits can predict the probability of success within components of reproductive success. Here, we measured sperm component traits (head length and flagellum length) and derived traits (total length and flagellum:head ratio) in free-living Mountain White-crowned Sparrows ( Zonotrichia leucophrys oriantha ) and examined how these morphological traits relate to extra-pair and within-pair reproductive components of reproductive success. We found no evidence for correlations between sperm morphology and total seasonal reproductive success. However, we did find that sperm morphology appeared to be associated with whether a male was successful at acquiring extra-pair offspring or defending his own paternity within his nest: males that achieved extra-pair success had longer flagella and longer total length of sperm cells compared to males that did not sire outside of their social nest. In contrast, males that successfully defended all paternity within their social nest tended to have shorter heads and larger flagellum:head ratios compared to males that lost paternity in their social nest. While these patterns suggest that different sperm traits may be linked to success in different components of reproductive success, they should be interpreted with caution given the exploratory nature of this study and limited sample size, and further investigation is warranted.